A new classification of C4-Atriplex species in Russia, with the first alien record of Atriplex flabellum (Chenopodiaceae, Amaranthaceae) from North Siberia - Sukhorukov, Alexander P. (PhytoKeys)
For a long time, the systematics ofAtriplex was based solely on morphological characters and leaf anatomy. The latest worldwide phylogenetic study of Atriplex significantly improved our knowledge about the relationships within the genus, but a new classification has not been put forward thus far. Here we re-evaluate the taxonomy of C4-species of Atriplex that are native to Russia. Seven species are classified into two sections, A. sect. Obione (incl. A. sect. Sclerocalymma, syn. nov.) (A. altaica, A. centralasiatica, A. rosea, A. sibirica, and A. sphaeromorpha), and A. sect. Obionopsis (incl. A. sect. Psammophila, syn. nov.) (A. fominii and A. tatarica). Although the majority of Eurasian C4-species have similar morphology, leafy inflorescence is a typical character for A. sect. Obione. The members ofA. sect. Obionopsis are characterised mostly by aphyllous inflorescences, but some species (A. laciniata, A. pratovii, and A. tornabenei) have leafy inflorescences. Geographically, almost all members ofA. sect. Obione are confined to Central Asia, although A. rosea is a typical Mediterranean element and A. argentea occurs in North America. The representatives ofA. sect. Obionopsis are distributed mostly in the Mediterranean and the Irano-Turanian floristic region. The alien status of A. rosea, A. sibirica and A. tatarica is discussed. Atriplex flabellum, a desert species from the Irano-Turanian region, is reported for the first time from Russia (Yamalo-Nenets Autonomous District, North Siberia) as a casual alien. This species occupies a phylogenetic position distant from both aforementioned sections. An identification key to all C4-species of the genus growing in Russia is given, and a sectional checklist with updated nomenclature and revised synonymy is provided.